The Ethiopian National eHealth Strategy and its Alignment with the Health Informatics Curriculum - Tilahun, Binyam; Zeleke, Atinkut; Kifle, Mengistu; Fritz, Fleur (Journal of Health Informatics in Africa, 2015)
Background: Many countries have developed eHealth strategies based on the WHO and ITU eHealth strategy toolkit. However, the success of the strategy, which appears to influence the diffusion of eHealth systems, is mainly dependent on the availability of skilled health informaticians at all levels. The purpose of this paper is therefore to review the Ethiopian eHealth strategy draft with respect to expertise requirements and to compare it with the graduate profile of the only bachelor in health informatics program in Ethiopia.Methods: A comparative analysis of the eHealth strategy with the curriculum of the bachelor in health informatics program was done. In the analysis, we identify the main focus areas of the eHealth strategy and compare its coverage in the academic and practical competency areas of the curriculum.Results: The eHealth strategy identifies five main areas of priorities for health information system implementations. They are: Health information systems, Telemedicine, mHealth, eLearning (for health workforce training) and community information systems. The curriculum contains 62 ECTS courses directly related to those areas. Additionally, the curriculum contains 89 ECTS for strategic and communication level skills, 108 ECTS for technical level skills, and 50 ECTS for monitoring and evaluation level skills.Conclusions: The eHealth strategy expertise and the curriculum are well aligned, especially regarding the technical level skills. The department and the ministry must work together so that the students get practical experiences of all the courses during their study.